Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17082756
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Continuous Improvement of Public Car-Sharing Platforms on Passenger Loyalty: A Mediation and Moderation Analysis

Abstract: Public car-sharing is a growing business model that contributes to sustainable transportation and urban development. The continuous improvement of public car-sharing platform to garner passenger loyalty is vital for a car-sharing platform’s success. This study applied perceived value theory, trust theory, and transaction cost theory to construct a structural equation model in order to explain passenger loyalty. Data from 755 surveys were collected using stratified sampling in mainland China. The estimated resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Similarly, Julsrud and Farstad (2020) reported that customers regarded B2C carsharing as (more) trustworthy and professional. According to Ma et al (2020), trust can affect customer loyalty both directly and indirectly, prompting service providers to address this challenge by eliminating factors that might lead to loss of customer trust, such as high transaction costs. Table 5 summarizes the main reported usage characteristics of carsharing customers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Julsrud and Farstad (2020) reported that customers regarded B2C carsharing as (more) trustworthy and professional. According to Ma et al (2020), trust can affect customer loyalty both directly and indirectly, prompting service providers to address this challenge by eliminating factors that might lead to loss of customer trust, such as high transaction costs. Table 5 summarizes the main reported usage characteristics of carsharing customers.…”
Section: Resultsmentioning
confidence: 99%
“…et al (2015), Costain et al (2012), de Lorimier and El-Geneidy (2013), Loose et al (2006), Sioui et al (2012) B2C: individual use for leisure trips B2B: work-related trips Trip activity Charoniti et al (2020), Jian et al (2017), Wu et al (2020a) A smaller car may suffice when commuting or traveling to a meeting; heavy-duty purposes (e.g. moving goods) may require a larger car Frequency of use Paundra et al (2017), M€ unzel et al (2019) Carsharing customers are not necessarily frequent users; many use the service only occasionally Multimodal mobility Ampudia-Renuncio et al (2020), Becker et al (2017a), Carrone et al (2020), Clewlow (2016), Mishra et al (2015), M€ unzel et al (2019)Frequent travelers tend to combine use of carsharing with other modes of mobility such as walking and biking Influence on car ownershipFirnkorn and M€ uller (2015),Jochem et al (2020),Ko et al (2019), LeVine and Polak (2019),Loose et al (2006) Some studies report evidence of a reduction in car ownership as a result of engagement in carsharing TrustHartl et al (2018),Julsrud and Farstad (2020),Ma et al (2020),Wilhelms et al (2017a) …”
mentioning
confidence: 99%
“…However, researchers go beyond the simple reason for the cause and effect of a relationship and try to understand what bridges causality (Rose et al, 2004, Amery andZumbo, 2008). A number of authors (Liu et al, 2020, Ma et al, 2020 pay close attention to the moderating variables in research. Moderator is a qualitative or quantitative variable that affects the direction or intensity of the relation of a predictive variable (independent) and another dependent one (MacKinnon, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…H1: TQM has a positive relation to the PS. Ma et al [20] indicated that service quality has a significant influence on customer loyalty. The aspects of the perceived quality, including the tangible objects, reliability, responsiveness, and empathy, had a positive effect on the potential PL [21].…”
Section: The Research Hypothesesmentioning
confidence: 99%
“…This is similar to Lin et al's (2004) results. Ma et al [20 showed that aspects of the perceived quality are related to customers' loyalty [20]. Moreover, the perceived quality has a close relationship with the expectation that their loyalty via satisfaction is indirectly a mediating factor [16].…”
Section: Hypotheses Testingmentioning
confidence: 99%